An Experimental Evaluation of Low‐Cost GNSS Jamming Sensors. Issue 1 (March 2017) - Dimc, Franc; Bažec, Matej; Borio, Daniele; Gioia, Ciro; Baldini, Gianmarco; Basso, Marco
Abstract: This paper presents experimental results obtained during live GNSS jamming tests performed in a road environment. Different jamming detection strategies are considered with specific focus on signal agnostic approaches where no stringent model assumptions are made for the detector design. A measurement station made of a commercial GPS high‐sensitivity receiver and an SDR front‐end was deployed and used to collect measurements in the presence of jamming. The tests were performed using three different jammers and considering the effects introduced by a vehicle moving at different speeds. The advantages and shortcomings of the different detection approaches are analyzed, and the most effective detection strategies are selected. Copyright © 2017 Institute of Navigation